Cardiac Troponin Specific Autoantibodies: Analytical Tools for Exploring Their Impact on Cardiac Troponin I Testing - Savukoski, Tanja (fi=Turun yliopisto|en=University of Turku|, 2014)
Cardiac troponin (cTn) I and T are the recommended biomarkers for the diagnosis and risk stratification of patients with suspected acute coronary syndrome (ACS), a major cause of cardiovascular death and disability worldwide. It has recently been demonstrated that cTn-specific autoantibodies (cTnAAb) can negatively interfere with cTnI detection by immunoassays to the extent that cTnAAb-positive patients may be falsely designated as cTnI-negative. The aim of this thesis was to develop and optimize immunoassays for the detection of both cTnI and cTnAAb, which would eventually enable exploring the clinical impact of these autoantibodies on cTnI testing and subsequent patient management. The extent of cTnAAb interference in different cTnI assay configurations and the molecular characteristics of cTnAAbs were investigated in publications I and II, respectively. The findings showed that cTnI midfragment targeting immunoassays used predominantly in clinical practice are affected by cTnAAb interference which can be circumvented by using a novel 3+1-type assay design with three capture antibodies against the N-terminus, midfragment and C-terminus and one tracer antibody against the C-terminus. The use of this assay configuration was further supported by the epitope specificity study, which showed that although the midfragment is most commonly targeted by cTnAAbs, the interference basically encompasses the whole molecule, and there may be remarkable individual variation at the affected sites. In publications III and IV, all the data obtained in previous studies were utilized to develop an improved version of an existing cTnAAb assay and a sensitive cTnI assay free of this specific analytical interference. The results of the thesis showed that approximately one in 10 patients with suspected ACS have detectable amounts of cTnAAbs in their circulation and that cTnAAbs can inhibit cTnI determination when targeted against the binding sites of assay antibodies used in its immunological detection. In the light of these observations, the risk of clinical misclassification caused by the presence of cTnAAbs remains a valid and reasonable concern. Because the titers, affinities and epitope specificities of cTnAAbs and the concentration of endogenous cTnI determine the final effect of circulating cTnAAbs, appropriately sized studies on their clinical significance are warranted. The new cTnI and cTnAAb assays could serve as analytical tools for establishing the impact of cTnAAbs on cTnI testing and also for unraveling the etiology of cTn-related autoimmune responses.

Akuutti sepelvaltimotautikohtaus (ACS, engl. acute coronary syndrome) on maailmanlaajuisesti merkittävä kuolleisuuden ja työkyvyttömyyden aiheuttaja. Sydänperäiset troponiinit (cTn, engl. cardiac troponin) I ja T ovat biomarkkereita, joita suositellaan ACS-potilaiden diagnosointiin ja riskiarviointiin. Hiljattain on kuitenkin osoitettu, että cTn:a tunnistavat autovasta-aineet (cTnAAb, engl. cTn-specific autoantibody) voivat negatiivisesti häiritä cTnI:n detektioon käytettäviä immunomäärityksiä; jopa siinä määrin, että cTnAAb-positiiviset potilaat voidaan virheellisesti luokitella cTnI-negatiivisiksi. Väitöstutkimuksen tavoitteena oli kehittää ja optimoida cTnI- ja cTnAAb-määrityksiä, jotka lopulta mahdollistaisivat autovastaaineiden kliinisen merkityksen arvioimisen. Ensimmäisessä julkaisussa tutkittiin cTnAAb-häiriön suuruutta erilaisissa cTnImäärityskonfiguraatioissa ja toisessa cTnAAb:iden molekulaarisia ominaisuuksia. Havainnot osoittivat, että cTnI-molekyylin keskiosan tunnistavat immunomääritykset, joita kliinisessä käytössä olevat määritykset pääasiassa ovat, kärsivät cTnAAbhäiriöstä, ja että häiriö voidaan välttää uudentyyppisellä 3+1-määrityksellä. Tässä määrityksessä hyödynnetään kolmea cTnI:n N-terminukseen, keskiosaan ja Cterminukseen sitoutuvaa sitojavasta-ainetta ja yhtä C-terminukseen sitoutuvaa leimavasta-ainetta. Tällaisen määrityskonfiguraation käyttöä tuki myös cTnAAb:iden epitooppikartoitus, jonka perusteella cTnAAb-häiriö kattaa koko cTnI-molekyylin, vaikka autovasta-aineet tavallisimmin sitoutuvat cTnI:n keskiosaan. Lisäksi tulokset osoittivat, että cTnAAb:iden spesifisyydessä voi olla merkittävää yksilöllistä vaihtelua. Tietojen perustella kolmannessa julkaisussa kehitettiin parannettu versio aikaisemmin julkaistusta cTnAAb-määrityksestä ja neljännessä herkkä, cTnAAbhäiriöstä vapaa cTnI-määritys. Väitöskirjatyön tulokset osoittivat, että ACS-epäillyistä potilaista noin joka 10:nnellä on verenkierrossaan havaittavia määriä cTnAAb:ita ja että cTnAAb:t voivat estää cTnI:n määrittämisen, kun ne sitoutuvat samoihin kohtiin cTnI:n immunodetektioon käytettävien vasta-aineiden kanssa. Näin ollen on mahdollista, että cTnAAb-häiriö johtaa tällaisten potilaiden virheelliseen luokitteluun. Koska cTnAAb:iden tiitterit, sitomisvoimakkuudet ja epitooppispesifisyydet sekä endogeenisen cTnI:n pitoisuus yhdessä ratkaisevat cTnAAb:iden lopullisen vaikutuksen, niiden kliinisestä merkityksestä tarvitaan lisätutkimuksia suuremmilla potilasaineistoilla. Kliinistä merkitystä selvitettäessä uudet cTnI- ja cTnAAb-määritykset voivat toimia tärkeinä analyyttisinä työkaluina.